Discharge of debt through consumer bankruptcy - Nowak, Paweł (Journal of Finance and Financial Law, 2025)
The purpose of the article. The purpose of the article is to assess the legal situation of the consumer debtor from the point of view of achieving the primary goal of bankruptcy proceedings, which is debt relief. The article presents the circumstances that a consumer applicant should take into account so that the risk of not being discharged from debt does not materialize. Methodology. The article is based on an analysis of the content of legal acts, the position of doctrine and studies of the literature on the subject. Results of the research. The conclusions of the article apply to consumer bankruptcy proceedings as a whole. The analysis shows that there is an evolution of the consumer bankruptcy model towards a liberal model, creating easy access to this institution. However, the liberalization of bankruptcy law has not completely eliminated the risk of declaring bankruptcy without achieving the consumer applicant's goal of debt relief. The regulations require the court to check whether equitable or humanitarian considerations will be violated in issuing an order refusing to establish a plan for repayment of creditors, or remitting the bankrupt's liabilities without establishing a plan for repayment of creditors, or conditionally remitting the bankrupt's liabilities without establishing a plan for repayment of creditors. This rigor is a fairly strong safeguard for the debtor's consumer against the risk of not being discharged of the debt but does not provide certainty.